Aplikasi Beberapa Pupuk Organik tTerhadap Produksi, Kualitas Buah dDan EfisiensiAgronomi Melon di Tanah Gambut - Pienyani Rosawanti; Nurul Hidayati; Fahruddin Arfianto; Djoko Eko Hadi Susilo (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This research aims to know the effect interaction of application of types and different dosage of organic fertilizers on production and fruit quality of melons on peatlands, effect of application of types and different dosage of organic fertilizers on production and fruit quality of melons on peatlands, and the agronomic efficiency of the use of several types and different dosage of organic fertilizers on production of melons on peatlands. This research design was used as a Randomized Block Design (RBD) consists of two factors with 4 replication. The first factor consisted of types of organic fertilizer (P) i.e. chicken manure (PA), guano manure (PG), and cow manure (PS). The second factor consisted of fertilizer dosage (D) i.e. 0 tons ha-1 (without fertilization, called control), D1 = 15 tons ha-1, D2 = 30 tons ha-1 and D3 = 45 tons ha-1. The data obtained by analysis of variance (ANOVA) or F test at α = 5% and 1% levels to determine the effect of treatment was tested further by HSD (honestly significant difference) testat the level of 5%. The result shows that the interaction type of organic fertilizer and the dosage of organic fertilizer treatment significant effect on the weight of the melon. Chicken manure is the best organic fertilizer on the size and quality of the melon. Dosage of 45 tons ha-1 organic fertilizer gave the highest results but it was not significantly different with a dosage of 30 tons ha-1. The use of chicken manure fertilizer of 30 tons ha-1 is more efficient in agronomy in increasing melons yield on peatlands.